Eksplorasi Etnomatematika pada Permainan Tradisional Bekles - Priyatna Hendriawan; Siti Faridah (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
The purpose of this study is to explore the ethnomathematical values ​​contained in traditional games in West Java, namely bekles or beklen. This study uses an ethnographic research design with a qualitative research approach. The object of this research is the rules of the game and the object of the game itself. The research subjects were two resource persons consisting of 1 child aged 8 years and 1 teenager aged 13 years. This research is located on Jl. Raden Soleh, RT 01 RW 05 Sindangsari Village, Kec. Kadupandak, Kab. Cianjur, West Java. Data was collected by using the methods of documentation, interviews, and observations. The results of this study indicate that there are ethnomathematical values ​​contained in traditional bekles games, namely the concept of integers from 1 to 10, the concept of modulu or remainder of division, the shape of the ball space, and probability. In addition, it can also be used as a problem in learning physics about the material of upper vertical motion and free fall motion. Based on the research results, it is known that the potential for ethnomathematics development in traditional bekles games is very large, which can be used as materials, teaching materials, or learning media such as student worksheets (LKPD).